Has the publication of cardiac surgery outcome data been associated with changes in practice in northwest England: an analysis of 25 730 patients undergoing CABG surgery under 30 surgeons over eight years. Issue 6 (19th January 2007) - Bridgewater, Ben; Grayson, Antony D; Brooks, Nicholas; Grotte, Geir; Fabri, Brian M; Au, John; Hooper, Tim; Jones, Mark; Keogh, Bruce
Abstract : Objectives: To study changes in coronary artery surgery practice in the years spanning publication of cardiac surgery mortality data in the UK. Methods: A retrospective analysis of prospectively collected data from all National Health Service centres undertaking adult cardiac surgery in northwest England was carried out. Patients undergoing coronary artery surgery for the first time between April 1997 and March 2005 were included. Changes in observed, predicted and risk adjusted mortality (EuroSCORE) were studied. Evidence of risk-averse behaviour was looked for by examining the number of patients at low risk (EuroSCORE 0–5), high risk (6–10), and very high risk (11 or more), before and after public disclosure. Results: 25 730 patients underwent coronary artery surgery during the study period. The observed mortality decreased from 2.4% in 1997–8 to 1.8% in 2004–5 (p = 0.014). The expected mortality (EuroSCORE) increased from 3.0 to 3.5 (p<0.001). The observed to expected mortality ratio decreased from 0.8 to 0.51 (p<0.05). The total number and percentage of patients who were at low risk, high risk and very high risk was 2694 (84.6%), 449 (14.1%) and 41 (1.3%) before and 2654 (81.7%), 547 (16.8%) and 47 (1.4%) after public disclosure, respectively, demonstrating a significant increase in the number and proportion of high risk patients undergoing surgery (p<0.001). Conclusions: Publication of cardiac surgery mortality data in the UK has been associated with decreased risk adjusted mortality on retrospective analysis of a large patient database. There is no evidence that fewer high risk patients are undergoing surgery because mortality rates are published.